1981
DOI: 10.1111/j.1432-1033.1981.tb05346.x
|View full text |Cite
|
Sign up to set email alerts
|

Glycoproteins of Platelet Membranes from Glanzmann's Thrombasthenia. A Comparison with Normal Using Carbohydrate-Specific or Protein-Specific Labelling Techniques and High-Resolution Two-Dimensional Gel Electrophoresis

Abstract: Platelets from Glanzmann's thrombasthenia patients and from normal donors were surface labelled by techniques specific for sugars (terminal sialic acid, penultimate galactose/N-acetylgalactosamine) and proteins (tyrosine-histidine residues). These labelled platelets were solubilized in sodium dodecyl sulphate and separated on a two-dimensional electrophoretic system [O'Farrell, P. H. (1975) J . Biol. Chem. 250,4007 -4021 ] first according to their isoelectric point (PI) and then according to their molecular w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

1983
1983
1987
1987

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 17 publications
2
15
0
Order By: Relevance
“…Gpl 10 has a tendency to dimerize, as was also observed for the platelet receptor 3 subunit, IHa (McGregor et al, 1981; J.J.Calvete, J.L.McGregor and J.Gonzalez-Rodrigues, submitted).…”
Section: Discussionmentioning
confidence: 53%
“…Gpl 10 has a tendency to dimerize, as was also observed for the platelet receptor 3 subunit, IHa (McGregor et al, 1981; J.J.Calvete, J.L.McGregor and J.Gonzalez-Rodrigues, submitted).…”
Section: Discussionmentioning
confidence: 53%
“…In addition, the autosomal recessive pattern of inheritence of thrombasthenia and the frequency of a specific membrane glycoprotein deficiency in this disorder (16), suggest that this disease may represent a deletion in a specific platelet membrane protein. Nevertheless, other studies have suggested a more global defect in platelet membrane proteins (20), and these data point to a second functional molecular defect in these platelets as well.…”
Section: Discussionmentioning
confidence: 83%
“…As these patients' platelets are deficient in the membrane glycoproteins GPIIb and GPIIIa (16,17) and as there is evidence that these glycoproteins complex together in association with fibrinogen (18), the GPIIb/IIIa complex has been tentatively identified as the fibrinogen receptor. Controversy persists, however, since it has been reported that thrombasthenic platelets have abnormalities in other surface glycoproteins (19) and one group has proposed that thrombasthenic platelets do indeed have receptors for fibrinogen, but are unable to expose them in response to agonist activation (20).…”
Section: Introductionmentioning
confidence: 99%